2015
DOI: 10.1097/mao.0000000000000746
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Verbal Communication Performance of Children Provided With Cochlear Implants or Hearing Aids

Abstract: Real-world verbal communication abilities of children with CIs are similar to those of children with moderate-to-severe hearing loss using amplification. Because hearing age significantly influences performance, children with moderate-to-severe hearing loss using HAs and implanted children catch up with children with mild hearing loss at a hearing age of approximately 3 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In addition, previous research has clearly demonstrated the benefit of a good SNR for speech understanding in children [Caldwell and Nittrouer, 2013;Gifford et al, 2011;Meister et al, 2015;Plasmans et al, 2016]. The use of hearing assistance technology for CI patients is therefore essential to improve speech recognition in classrooms.…”
Section: Exposure Environmentsmentioning
confidence: 99%
“…In addition, previous research has clearly demonstrated the benefit of a good SNR for speech understanding in children [Caldwell and Nittrouer, 2013;Gifford et al, 2011;Meister et al, 2015;Plasmans et al, 2016]. The use of hearing assistance technology for CI patients is therefore essential to improve speech recognition in classrooms.…”
Section: Exposure Environmentsmentioning
confidence: 99%
“…As a result, 10 articles that met the inclusion criteria were analyzed, of which 10% were from 2011 (Clark et al 2011), 2012 (Nittrouer et al 2012), 2015 (Meister et al 2015) and 2017 (Zhong et al 2017). 20% were from 2010 Twelve instruments were identified in the methodology section of the 10 articles analyzed and due to the variability of the instruments, we decided to report them in categories according to the purpose of the instruments as shown in…”
Section: Resultsmentioning
confidence: 99%
“…The FAPCI instrument has been translated into Portuguese (Vassoler & Cordeiro 2015), German (Grugel et al 2009) and Korean (Lee et al 2009). In addition, as the FAPCI instrument contains items looking into the basic elements of verbal communication of children and the availability of normative data, it is suitable for assessing children using amplification (Meister et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…eTable 1 in the Supplement reports the relevance and validity assessment of the 21 selected studies . Relevance assessment showed that 2 of 21 studies (10%) included HA users with severe HI.…”
Section: Resultsmentioning
confidence: 99%